APLIKASI TEORI POS-STRUKTURALISME DALAM SEBUAH DISERTASI - Made Jiwa Atmaja (Journal Social and Humaniora, 2017)
This paper seeks to understand the application of structuralism theory in a dissertation that examines the novels of Balai Pustaka tradition. E?orts to understand the application of such a theory require the method of deconstruction readings, thereby disclosing the theoretical concept’s background, theoretical modification abilities and operational theories and methods. This is important because generally the works of academics have a weakness in the ability of theory modification and operational weaknesses over the theoretical concepts. Keywords: concept, method and post-structuralism